Gagasan Zuhud Modern dan Relevansinya dalam Upaya Peningkatan Etos Kerja Kaum Sufi - Rosi Islamiyati; Siti Amallia (Jurnal Multidisiplin Ibrahimy, 2024)
Islam teaches about a principle of balance in life. Excessive inequality on one side will result in not being in line with the mission of Islamic teachings. Like the problems of the world that should be balanced with the problems of the hereafter. The idea of zuhud in classical Sufism was interpreted as an effort to distance oneself from worldly matters and to focus more on the afterlife. As a result, this greatly affects the work ethic of the Sufis who regard worldly matters as lowly. The spirit of worship is not in line with the spirit of increasing the economy. The dynamics of concept development in explaining the meaning of zuhud has shifted from time to time. Zuhud in modern times began to discuss social, political, legal and economic issues. This research is a qualitative research using historical analytical methods to review the thinking paradigm of the Sufis in interpreting zuhud from classical to modern times and relating it to contemporary problems as capital for efforts to improve the work ethic of Sufis. Thus a conclusion is obtained that the idea of modern asceticism does not mean refusing wealth that comes to him. Rather, wealth must be picked up as a bridge to its closeness to God. The spirit of work ethic is interpreted as a manifestation of sincerity which is the maqomat in Sufism. In the end, this is what causes Sufism to be known more openly. Not only discussed in mosques or quiet places, Sufism is now widely discussed in public in the form of seminars. In fact, the term "sufi with a necktie" has even emerged as a designation for Sufis who harmonize economic life with the affairs of the hereafter.